PENERAPAN MODEL PEMBELAJARAN KOOPERATIF SCRIPT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN IPS KELAS VII DI SMP TAKHASSUS AT-TAUHID MADURA - Yuliyah; Ika Lis Mariatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The selection of the right method will guide students towards the correct way so that their understanding is also optimal and their learning outcomes are maximized. The method that the author is researching is the cooperative script method, where students work in pairs and take turns summarizing parts of the material being studied. The problem that arises in this study is that students' learning outcomes in social studies are unsatisfactory, due to the teaching method used by the teacher still relying on lecturing, which dominates the learning process and makes students appear passive and bored. Therefore, the researcher applied the cooperative script method to improve the learning outcomes of seventh-grade students at SMP Takhassus At-Tauhid Madura. This research aims to determine the implementation of learning using the cooperative script model in improving the learning outcomes of seventh-grade students at SMP Takhassus At-Tauhid Madura and to find out how much improvement occurs The learning outcomes of seventh-grade students at SMP Takhassus At-Tauhid Madura after participating in geography lessons using the cooperative script model. This research employs the Classroom Action Research (CAR) method, with the instruments used being: Student Worksheets (LKPD), tests, and documentation. The subjects of this study are 11 seventh-grade students at SMP Takhassus At-Tauhid Madura. Based on the issues above, there is a need for intervention to achieve the learning outcomes of students in explaining economic material in their surroundings. This study consists of 2 cycles, namely Cycle 1 and Cycle 2. Thus, it can be concluded that learning using the cooperative script model can improve student learning outcomes in social studies subjects. This result can be seen from the differences between Cycle 1 and Cycle 2; in Cycle 1, the average score of student learning outcomes reached 63.6%, and in Cycle 2, the average score increased to 81.8%. From here we can see that the implementation of the cooperative script learning model has been carried out very well.